Role of A.I in Surgery; a Letter to editor - Mohammed Ridha H .Alhakeem (BULLET : Jurnal Multidisiplin Ilmu, 2022)
Dear Editor, The use of artificial intelligence in surgery is expanding every day. In the past, there was a dearth of knowledge about the potential uses of robots in surgery, which was primarily based on the misconception that robots were taking the place of human surgeons while, in fact, their function was more like that of a supplement than a replacement [1-5]. A number of new directions in robotic and AI-enhanced surgery have emerged as a result of this attitude shift. Even if it took longer to examine its promising results, the steadily expanding research in this area has revolutionized how healthcare is provided over the past few years [6-10]. Robotic surgery is already very important since it has considerably decreased surgical problems brought on by trauma and has improved patient recovery, shortening hospital stays [11, 12]. AI has also shown some promise in terms of analyzing, storing, and analyzing patient records, and this has proven to be helpful in some cases. By transmitting the motions of the surgeon's hands to the surgical target through tremor-filtered movements of the surgical tools, conventional robots have complemented surgeons. The likelihood of a patient experiencing intraoperative trauma has considerably decreased as a result [13-15]. Further study in this area has shown encouraging results, including parts of machine learning like Learning from Demonstration and Reinforcement Learning that have opened up new possibilities for surgical robots to react to human activities [16]. This significant development is a result of recent developments in cloud computing, big data analytics, and artificial intelligence. Robots with AI assistance have already been employed in a number of surgical procedures [17,18,19]. In laparoscopic procedures, surgical robots that operate depending on the movement of the surgeon's head are helping. Similar to this, there are literary examples of robots that operate depending on facial, gaze, and gesture movements [20,21]. Robots with AI assistance have been employed in heart surgery, hair transplant procedures, and blood vessel suturing. By the end of the twenty-first century, clinically useful surgical robots are probably a reality [22, 23, 24],. Artificial intelligence and surgical robotics can be combined to expand surgical capabilities, improve patient access to care, and improve surgical results. We concur with the authors and anticipate that the use of AI in surgery will grow in the future [25-28].